PENGARUH PERILAKU BERKARAKTER SISWA KELAS VIII TERHADAP HASIL BELAJAR PPKN DI SMP NEGERI 1 TEMPULING KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Juraidah '; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research is motivated by the process of teaching and learning activities that are part of the educational process, but in the process of teaching and learning takes many students bored and out of the classroom during class hours, To form a good character is not enough just to go through the process of learning in the classroom Citizenship, but it must also be accompanied by good habits performed in daily life. Teach character values not only at the cognitive level, but touches on internalization, and the real practice in the lives of young people in the community every day. At each school the student learning outcomes in get KKM sometimes substandard schools or some children are not in either study results obtained from the daily tests and exams semester. The wording in this study is